The relationship between management styles and trainers’ job motivation in the public institutions - Nedim Malkoc; Suzan Dal (International Journal of Evaluation and Research in Education (IJERE), 2021)
The study aimed to determine the relationship between perceptions of management styles and trainers' motivation in the public sports institutions, and to examine the effect of management styles on job motivation. The sample of the research consists of 190 trainers, 18 of whom are women and 172 of whom are men working in the public sports institutions. In the study, descriptive scanning method was used, and the data obtained were analyzed by making statistical procedures such as frequency, correlation, regression analysis. It was found that democratic management style and paternalist management style had a positive effect on trainers’ job motivation. However, the liberal management style and authoritarian management style were found to have a negative effect on trainers’ job motivation.